KONFLIK GAM-RI DAN KERENTANAN PANGAN MASYARAKAT TRANSMIGRAN - Amiruddin Ketaren; Pangeran Putra Perkasa Alam Nasution (Universitas Andalas, 2018)
This article presents a narrative snippet of circumstances of the food security over the Javanese transmigrants during the Acehnese Freedom Movement (GAM) vs Indonesian Government (NKRI) conflict. The data presented through a case study in Cot Girek sub-district, Aceh Utara district, Aceh. The article ellaborates food availability strategies during the conflict, food accessibility, food security. The narration in this article is presented based on data obtained by qualitative research methods. Primary data obtained by interview (in-depth). The narrative notion in this paper propose that conflict often occurs as a result of some past memories coverage racial exclusion, religion, to political and economic discrimination; including the seizure of strategic resource controls, such as land, water, trade routes, and mineral deposits of the earth.Dissatisfaction that encompasses the disparity of land distribution and discriminatory economic policies that hinder decent living standards for every community. Tensions escalate into violent conflicts especially as economic conditions worsen and people face a subsistence crisis. Conflict is created when everyone feels that they have nothing to lose and are therefore willing to fight for resources, political power, and cultural respect. It is fitting for all parties to ensure social integration in the proper arrangement of economic and political distribution and in the spirit of equality. On the issue of food security, the goal is to create conditions for everyone at any time to gain food to support survival.